1
$\begingroup$

The electromagnetic dual tensor is given by \begin{align} \tilde{F}^{\mu\nu}=\frac{1}{2}\epsilon^{\mu\nu\delta\rho}F_{\delta\rho} \end{align} Here, $\epsilon^{\mu\nu\delta\rho}$ is the Levi-Civita symbol. I want to show that $$ \partial_{\mu}\tilde{F}^{\mu\nu}=0 , $$ using the antisymmetric propeties of Levi-Civita.
I have exchanged indices $\rho \to \delta$, \begin{align} & \frac{1}{2}\partial_{\mu}\epsilon^{\mu\nu\rho\delta}F_{\rho\delta}\\ &=- \frac{1}{2}\partial_{\mu}\epsilon^{\mu\nu\delta\rho}F_{\rho\delta}\\ &=\frac{1}{2}\partial_{\mu}\epsilon^{\mu\nu\delta\rho}F_{\delta\rho} \end{align} In the last line, I've used $F_{\mu\nu}=-F_{\nu\mu}$. So, I can't use the property to prove this. In Ryder's QFT book he says that, because of the antisymmetry of $\epsilon^{\mu\nu\delta\rho}$ this will be true.

$\endgroup$
0
$\begingroup$

We know that $$ F_{\mu \nu} = \partial_\mu A_\nu - \partial_\nu A_\mu . $$ Now we get $$ \partial_\mu \epsilon^{\mu\nu\sigma\rho} F_{\sigma \rho} = \partial_\mu \epsilon^{\mu\nu\sigma\rho} ( \partial_\sigma A_\rho - \partial_\rho A_\sigma ). $$ Now, from symmetry/antisymmetry we have $$ \epsilon^{\mu\nu\sigma\rho} \partial_\mu \partial_\sigma A_\rho = 0 $$ and similar for the other term. To see this last step, consider $$ \epsilon^{\mu\nu\sigma\rho} \partial_\mu \partial_\sigma = [\textrm{rename variables } \sigma \leftrightarrow \mu] \\ = \epsilon^{\sigma\nu\mu\rho} \partial_\sigma \partial_\mu = [\textrm{use property of Levi-Civita } \epsilon^{\alpha \beta} = -\epsilon^{\beta \alpha}] \\ = - \epsilon^{\mu\nu\sigma\rho} \partial_\sigma \partial_\mu = [\textrm{use that } \partial_\alpha \partial_\beta = \partial_\beta \partial_\alpha] \\ = - \epsilon^{\mu\nu\sigma\rho} \partial_\mu \partial_\sigma . $$ So we have $$ \epsilon^{\mu\nu\sigma\rho} \partial_\mu \partial_\sigma = - \epsilon^{\mu\nu\sigma\rho} \partial_\mu \partial_\sigma . $$ And if $a = -a$ then we must have $a = 0$.

$\endgroup$
  • 1
    $\begingroup$ Added a (perhaps overly detailed) explanation of the last step, but that simply follows from the theorem that the contraction between a symmetric and antisymmetric tensor is zero. $\endgroup$ – JezuzStardust Sep 17 '19 at 20:58
1
$\begingroup$

In the parlance of differential forms, the identity (Abelian Bianchi identity) amounts to $$ dF = 0. $$ This is a trivial fact in math: exact forms ($F = dA$) are closed $$ dF = d^2A = 0, $$ because of nilpotency of $d$ ($d^2 = 0$, barring Nonholonomic coordinates).

Note that the opposite may not be true: closed forms ($dF = 0$) do not necessarily imply exact forms ($F = dA$). Case in point: non-trivial de Rham cohomology.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.